Association of the serum uric acid to creatinine ratio with metabolic syndrome in the middle age and older population in China - Zhong, Danrong; Liu, Dongchen; Guo, Yongtian; Huang, Haoyin; Li, Lu; Wu, Fangqin; Huang, Suli (Frontiers in Endocrinology, 2022)
Abstract Background: Metabolic syndrome (MetS) has attracted great interests, with an increasing prevalence. Recent studies showed that serum uric acid to creatinine ratio( SUACr) might be an excellent biomarker for Mets risk prediction in diabetes patients and postmenopausal women. However, the relationship between SUACr and Mets in in the mid-age and older populatoin remains unclear. Methods: A total of 1277 participants were included in this cross-sectional study. Logistic regression model was performed to assess the association between SUACr and MetS in the total population. The dose-response relation of SUACr and MetS was further assessed by the restricted cubic spline model (RCS). Furthermore, to explore the relationships between levels of SUACr and the number of metabolic components, analysis of covariace (ANCOVA) was applied. Results: The levels of SUACr were lower in the MetS subjects (P<0.001, OR=1.60, 95%CI=1.36-1.89). Positive relationship and dose-response manner was further confirmed by the RCS model. We also found that with increased number of components, the levels of SUACr tended to increase. Moreover, levels of SUACr were strongly related to triglyceride (TG), Body mass index (BMI), blood glucose, Systolic blood pressure/Diastolic blood pressure (SBP/DBP) and hypertension. In addition, the positive association between SUACr and MetS also occurred in those with normal uric acid levels. Conclusion: Elevated levels of SUACr was strongly associated with an increased risk of MetS, such positive relation still remained in those with normal uric acid levels individuals.